Transcending the Cutaneous Barrier Through Nanocarrier Exploration for Passive Delivery of Anti-hypertensive Drugs: A Critical Review - Kumar, Lalit; Utreja, Puneet (Recent Patents on Nanotechnology, 2020)
Background: Hypertension comes under the category of chronic disease, which requires long term treatment. Hypertension is usually treated by oral administration of various therapeutic agents. There are several limitations of the oral route, making pharmaceutical scientists to discover an alternative route for drug delivery. Methods: The transdermal route may be a better alternative as it shows various advantages like lack of first-pass effect and high patient compliance. The skin may act as a primary barrier for the transdermal delivery of anti-hypertensive drugs; therefore, new approaches are required to cross this barrier. Nanocarrier systems come under these new approaches to cross the skin barrier. Various nanocarrier systems explored for transdermal delivery of antihypertensive drugs are liposomes, elastic liposomes, ethosomes, transethosomes, oleic acid vesicles, niosomes, solid lipid nanoparticles, nanostructured lipid carriers, nanoemulsions/microemulsions, and carbon nanotubes. Results: This review summarizes the potential of advanced nanocarrier systems for effective management of hypertension following the transdermal route. The entire literature search regarding the utility of nanocarrier systems in transdermal delivery of antihypertensive drugs was done by using Pubmed and Google Scholar. Conclusion: Nanocarrier systems are capable of reducing various drawbacks of conventional formulations of antihypertensive drugs like excessive first-pass effects, high dosing frequency, and toxicity promoting high patient compliance. However, the clinical efficacy determination of such nanocarrier systems is still a challenge and it will govern their presence in the global pharmaceutical market.
Keywords: first pass effect